ANALISIS PENGARUH INOVASI PRODUK, PERSEPSI HARGA TERHADAP PROSES KEPUTUSAN PEMBELIAN PADA WARUNG MAKAN DI DESA WISATA DANAU LAU KAWAR KECAMATAN NAMAN TERAN KABUPATEN KARO - Sri Rosliana Lubis (Jurnal Ilmiah Akomodasi Agung, 2023)
This study aims to determine the effect of product innovation, price perception on the Purchasing Decision Process at Food Stalls in the Lake Lau Kawar Tourism Village, Naman Teran District, Karo Regency. The characteristics of the sample are explained by quantitative methods, and the research results are exhibited with tables, graphs, and narratives. The research sample consisted of one hundred participants who were purposively selected. Data was obtained through a questionnaire containing questions relating to the respondent's profile. The results and conclusions of the study indicate that the independent variables of product innovation, price perception, and location are 37.1% responsible for the dependent variable of the purchasing decision process. The adjusted coefficient of determination, or (R2), is 0.371. While the last 62.9% is covered by additional variables not included in this model. Where purchasing decisions at food and beverage stalls in the Lake Lau Kawar tourist village, Karo Regency are influenced by product innovation, price perceptions, and location.